Prospects and possibilities of introducing a common currency in SAARC countries - Chowdhury, Anup; Chowdhury, Saman Paul; Haque, Shamim Ehsanul (BRAC University, 2010)
The growth of regional economic cooperation arrangement is one of the major developments in the post World War II period. The formation of regional integration has been greatly successful in bringing historically hostile countries together. The classic example is the state in the European Union and the South East Asia where economic dimensions have brought long time foes in the same dais. The basic premise on which SAARC was founded was that by activating cooperative cultural identities and economic interests, political conflicts and tensions in South Asia could be moderated, if not completely eliminated. It looks advantageous if SAARC countries could adopt a single currency-substantially enhancing their bargaining power together in the world market. In this paper drive has been made to analyze the possibilities and benefits of a single currency in SAARC countries. A common currency’s attraction is that it doesn’t represent the currency of any single country. It’s advantageous to deal with a lesser number of currencies since each time one converts a currency there is a huge loss. The common currency regime, when achieved, can present substantial benefits to the region. With uncertainty about exchange rates removed, and transaction costs reduce trade and investment in the region can get a big boost. Also with money creation under regional guidelines, there would be better prospects of synchronization of inflation, interest rate and GDP growth, all of which can contribute to accelerated growth and poverty reduction.